IMPLEMENTATION OF HOUSING AND RESIDENTIAL AREA DEVELOPMENT THROUGH REJUVENATION OF THE KEDAUNG AREA IN CREATING A LIVABLE CITY IN TANGERANG CITY - Aini Timur; Tedi Gunawan; Suparman (Jurnal Ilmiah Wahana Bhakti Praja, 2025)
This research discusses the development of housing and residential areas through the construction of flats in Kedaung, Tangerang City, as a response to rapid urbanization and the challenges of slum areas. The aim of the research is to evaluate the success of the program in improving the quality of life of the community and overcoming the problem of slum settlements in accordance with the objectives of SDGs No. 11. This research uses Charles O. Jones' theory of policy implementation which includes organizing, interpreting and implementing, and applies descriptive and qualitative methods with primary and secondary data collection. The research results show that through the rejuvenation program, the slum conditions in Kedaung have been successfully improved from moderate slums to light slums, even zero value by the end of 2023. Collaboration between the Ministry of Public Works and Public Housing (Ministry of PUPR) and the Tangerang City Government in infrastructure planning and development, as well as economic intervention programs, has contributed to improving the quality of life of the community and strengthening local cultural identity.